Numerical modeling of electromagnetic wave propagation in spatially-varying evaporation duct conditions via 3D parabolic equation method - Hanjie Ji; Hanjie Ji; Lixin Guo; Yan Zhang; Tianhang Nie; Yiwen Wei; Jinpeng Zhang; Qingliang Li; Xiangming Guo; Yusheng Zhang (Frontiers in Marine Science)
This study numerically investigates electromagnetic (EM) wave propagation in spatially-varying evaporation ducts over rough sea surfaces. Conventional two-dimensional (2D) models assume homogeneous refractive index distribution along the cross-range dimension in a single propagation plane, limiting their ability to capture the 3D spatial heterogeneities present in real-world scenarios. Under significant horizontal gradient variations in evaporation ducts, EM wave propagation effects across the cross-range dimension become significant. We investigate an advanced 3D parabolic equation (3DPE) framework that synergistically integrates anisotropic refractive profiles with sea-surface roughness characterization. An even-odd splitting Fourier transform algorithm enables efficient computational analysis of EM wave propagation across azimuthal planes. Quantitative analysis reveals that the 3DPE framework delivers over 40% performance improvement compared to the 2D model. This approach significantly enhances predictive accuracy for over-the-horizon radar assessments in maritime environments, providing crucial support for optimizing next-generation communication systems.